Population Pharmacodynamic Model of Neutrophil Margination and Tolerance to Describe Effect of Sarilumab on Absolute Neutrophil Count in Patients with Rheumatoid Arthritis - Pavel Kovalenko; Anne Paccaly; Anita Boyapati; Christine Xu; Gregory St John; Michael C. Nivens; John D. Davis; Ronda Rippley; A. Thomas DiCioccio (Wiley, 2020)
Evidence suggests that effects of interleukin‐6 pathway inhibitors sarilumab, tocilizumab, and sirukumab on absolute neutrophil count (ANC) are due to margination of circulating neutrophils into rapidly mobilizable noncirculating pools. We developed a population pharmacodynamic model using compartments for neutrophil margination and ANC‐specific tolerance to describe rapid, transient ANC changes in blood following administration of subcutaneous sarilumab and intravenous/subcutaneous tocilizumab based on data from 322 patients with rheumatoid arthritis in two single‐dose (NCT02097524 and NCT02404558) and one multiple‐dose (NCT01768572) trials. The model incorporated a tolerance compartment to account for ANC nadir and beginning of recovery before maximal drug concentration after subcutaneous dosing, and absence of a nadir plateau when the ANC response is saturated after subcutaneous or intravenous dosing. The model effectively describes the ANC changes and supports neutrophil margination and tolerance as an explanation for the absence of increased infection risk associated with low ANC due to interleukin‐6 pathway inhibitor treatment.